AWARENESS OF EMERGENCY CONTRACEPTION AMONG MEDICAL STUDENTS - Dr SHIVALI RAI; MISS DHIVYAA. T; Dr KRISHNAN. V (International Journal of Pharma and Bio Sciences, 2016)
This study was conducted to assess the awareness and knowledge of emergency contraceptive pills, among Medical students and to assess the knowledge of the ill effects of illicit use of emergency contraception MBBS students of Saveetha Medical College were taken after obtaining informed consent . . It’s a descriptive Cross sectional study with a duration of 2 months. Data collection was done with a self-administered questionnaire with a sample size of 385.Results showed the awareness of emergency contraception among first year MBBS was 49% (girls) and 58% (boys) which, increased progressively to 100% among CRRI. 92% of boys and 70% of girls felt it can be used regularly without side effects in first year but, CRRIs knew its side effects From our study, we emphasize to introduce the curriculum on contraception and emergency contraception in early education itself.